Pengaruh Kebijakan Otonomi Khusus Papua Terhadap Pembangunan Prasarana Pendidikan dan Kesehatan di Kabupaten Manokwari Selatan, Provinsi Papua Barat - Kadam, Andarias; Setiadi, Rukuh (Jurnal Pembangunan Wilayah dan Kota, 2021)
This research is a descriptive study combining qualitative and quantitative approach. It compares infrastructure development before and during the special autonomy era. The main focus of this research is the special autonomy policy for education and health development in South Manokwari Regency. This study discusses "whether the special autonomy policy is able to improve the development of education and health in West Papua Province, especially South Manokwari Regency? In particular, this paper aims to understand the influence of special autonomy has on the development of education and health in South Manokwari Regency. A number of indicators or criteria used in this study include: (i) availability, (ii) quality, (iii) accessibility, (iv) utilization and implications. The data needed in this research come from two sources, namely primary data collection through written and oral questions from respondents in the research area and secondary data from record sources, government publications, BPS statistical data, Bappenas and other related data sources. The results of the analysis show that there have been some progress in the development of education and health infrastructures. As an implication, the achievement of the human development index has continued to increase from 2013 to the present. However, there are a number of notes. First, the availability of educational facilities on average remains limited, both in terms of facilities and teaching staffs. Second, quality is still an issue, for example in 2017 around 15% of school facilities were in a poor condition. The percentage of primary school teachers who have qualifications (67.6%) is still far below that of secondary school teachers at 92.3%. Likewise, the maternal and child mortality rates are still high, and the ratio of health workers is still low. Third, as the distance between villages are relatively remote one another, the service range of each facility ranges from 2-5 kilometers or more. The following are about institutional issues and aspects of inter-sectoral governance that must be fixed immediately so that the derivative of laws in local regulations can produce special programs or policies that can be realized and targeted to the root of the problem so that development can be effectively and holistically in the implementation of decentralization system used by the current government.Â